Time course of collagen peak in bile duct-ligated rats - (:unkn) unknown (BIOMED CENTRAL LTD, 2011)
Background: One of the most useful experimental fibrogenesis models is the bile duct-ligated rats. Our aim was to investigate the quantitative hepatic collagen content by two different methods during the different stages of hepatic fibrosis in bile duct-ligated rats on a weekly basis. We questioned whether the 1-wk or 4-wk bile duct-ligated model is suitable in animal fibrogenesis trials. Methods: Of the 53 male Wistar rats, 8 (Group 0) were used as a healthy control group. Bile duct ligation (BDL) had been performed in the rest. Bile duct-ligated rates were sacrificed 7 days later in group 1 (10 rats), 14 days later in group 2 (9 rats), 21 days later in group 3(9 rats) and 28 days later in group 4 (9 rats). Eight rats underwent sham-operation (Sham). Hepatic collagen measurements as well as serum levels of liver enzymes and function tests were all analysed. Results: The peak level of collagen was observed biochemically and histomorphometricly at the end of third week (P < 0.001 and P < 0.05). Suprisingly, collagen levels had decreased with the course of time such as at the end of fourth week (P < 0.01 and P < 0.05). Conclusion: We have shown that fibrosis in bile duct-ligated rats is transient, i.e. reverses spontaneously after 3 weeks. This contrasts any situation in patients where hepatic fibrosis is progressive and irreversible as countless studies performed by many investigators in the same animal model.
Keywords: Bile duct-ligated rat; fibrosis; fibrogenesis; liver; collagen; reversible; BILIARY-OBSTRUCTED RATS; INDUCED LIVER FIBROSIS; HEPATIC-FIBROSIS; INTERFERON-ALPHA; VITAMIN-E; DAMAGE; PROLIDASE; CIRRHOSIS; INJURY; MODEL